Juridical Analysis of Constitutional Court Decision No. 119/PUUXXIII/2025: Strengthening the Protection of Human Rights and The Environment In Indonesia - Suhartoyo Suhartoyo (Journal Of Social Science (JoSS), 2025)
This study aims to conduct a normative juridical analysis of environmental criminal law in Indonesia, the protection of human rights within the Indonesian legal framework, and the implications of Constitutional Court Decision Number 119/PUU-XXIII/2025 in reinforcing human rights and environmental protection. Employing a case study approach, this research utilizes normative juridical methodology. The findings indicate that environmental criminal law in Indonesia is governed by several limitations, including regulatory deficiencies, inadequate public awareness, and insufficient law enforcement. The Constitutional Court Decision Number 119/PUU-XXIII/2025 represents a significant step towards strengthening human rights and environmental protection. John Rawls' theory of justice is applied to examine the implementation of law and bolster the protection of human rights and the environment. This study is expected to contribute to the understanding of environmental criminal law and human rights protection in Indonesia, as well as provide recommendations for enhancing the implementation of environmental criminal law and human rights protection in Indonesia.